Single point of failure : the ten essential laws of supply chain risk management - Lynch, Gary S. (Gary Scott), 1958- (Hoboken, N.J. : Wiley, 2009)
"Expert guidance for establishing an organization's supply risk management program Single Point of Failure: The 15 Laws of Supply Chain Risk Management offers insider guidelines for managing the risk of supply chains gained from customer success and failures. Analyzing and providing recommendations for various supply chain functions and risk, this book includes risk associated during various states of procurement, logistics/transportation, and manufacturing, warehousing and sales. Author Gary Lynch reveals the 15 key laws to mind when managing the risk of supply chains gained from customer successes and failures, as well as how to avoid bad decisions, and gather better information to make decisions. Gary S. Lynch, CISSP, (Mendham, NJ) is Managing Director and Practice Leader for the Risk & Resiliency Strategies Practice at Marsh"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business logistics; Risk management